Tiempo del uso del celular y desarrollo integral en niños de la Cuna-Jardín Aserrín Aserrán, Iquitos 2024 - Manuyama Silvano, Diana Karol (2025)
The objective of this study was to relate cell phone use time and comprehensive development in children from the Cuna Jardín Aserrín, Iquitos 2024. The research covered a population of 92 children who made up the study sample. A relational methodology was adopted, with a field, transversal and bivariate design. For data collection, a questionnaire and an observation guide based on the Battelle Development Inventory were used, applying survey and observation techniques, respectively. The results show an inverse and statistically significant relationship between cell phone use time and comprehensive child development. The inferential analyses, based on Kendall's Tau-b coefficient (-0.295, p = 0.001) and Spearman's rho test, together with Student's t (-6.039; p = 0.000), confirm that a longer exposure time to cell phones is associated with less comprehensive development. These findings validate the research hypothesis and underline the importance of regulating the use of electronic devices in early childhood to promote optimal comprehensive development.